Reka Bentuk Jangka Kuasa Mudah Alih - Lau, Kung Hui (Universiti Sains Malaysia, 2006)
A power meter basically is a meter that performs its duty as a device that gives a reading of power across an arbitrary load. In other words, it works just like a voltmeter or a multimeter that uses its two terminals as sensors to read the differential voltage across the terminal. Unlike a voltmeter or a multimeter, this device computes and displays the Vrms, Irms and instantaneous power at the same time. The word ‘portable’ brings the meaning of the ease to carry or to move around. Thus, this design is not just emphasizes on the ability of high precision for instantaneous power measurement, but also in designing it to become highly portable. Throughout the years, power meters are developed via different methodologies. These methodologies include electrodynamics, electrostatics, thermal and Hall effects power meter. Basically, these power meters all have a common approach in dealing with the voltage and current value obtained from sensors. This approach is to perform analog multiplication on these two parameters. In the 1970s, Raymond S. Turgel introduced power meter using sampling method, where the voltage and current are sampled separately, digitized and then the power is computed using a computer. As an overall, this power meter is designed using sampling technique, where the signal is measured and digitized using a microcontroller PIC 16F877. The values for Vrms, Irms and the instantaneous power are then computed from the microcontroller as well they are displayed on the LCD screen. During testing and verification period, a sine wave with a known frequency is applied to it. This power meter showed a remarkable result with accuracy up to 95%.